Discourse on culture in research on immigrant and migrant workers' health. Issue 6 (20th May 2019) - Premji, Stephanie
Abstract: Background: Health and safety researchers and practitioners have proposed that cultural differences help explain inequalities between foreign and native‐born workers. While cultural explanations for inequalities have long been debated in other fields, there exists little critique of cultural discourses in occupational health. Methods: This article examines and discusses the discourse on culture in 107 articles on immigrant or migrant workers' health published between 2011 and 2015. For each article, passages on culture were identified and analysed for both the context and the manner in which culture was discussed. Results: The discourse on culture was found to be generally simplistic, individualistic, and uncritical, intentionally or unintentionally supporting the worldview that workers' "otherness" is both cause of inequalities and target for interventions. Conclusion: The article argues that empirical, theoretical and interdisciplinary work is needed to document the mechanisms and pathways that underlie health and safety inequalities by foreign‐born status.